2018
DOI: 10.1159/000492611
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Damage by Firecracker Trauma

Abstract: Firecrackers are still popular among the general public of various populations worldwide. This study investigated inner ear damage in patients with firecracker trauma and analyzed noise levels in 6 kinds of commercially available firecrackers. During the past 20 years, we have experienced 30 patients with firecracker trauma. An inner ear test battery comprising audiometry, cervical and ocular vestibular-evoked myogenic potential (cVEMP and oVEMP) tests and a caloric test was performed. The real-time noise leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
8
0
7
Order By: Relevance
“…Not only the speed and force of impact are responsible for firecracker injuries but they are also implicated for inner ear damage due to noise. It is seen that mean hearing levels at high frequencies (4000 and 8000 Hz) were significantly higher than those at the low and middle frequencies, thus indicating that firecrackers mostly cause high-tone hearing loss [10]. A similar case report has been reported in the literature, with a 7-year-old child while using illegal fireworks presented with a superficial laceration on the belly, intestinal perforation, and extensive hand injuries.…”
Section: Discussionsupporting
confidence: 59%
“…Not only the speed and force of impact are responsible for firecracker injuries but they are also implicated for inner ear damage due to noise. It is seen that mean hearing levels at high frequencies (4000 and 8000 Hz) were significantly higher than those at the low and middle frequencies, thus indicating that firecrackers mostly cause high-tone hearing loss [10]. A similar case report has been reported in the literature, with a 7-year-old child while using illegal fireworks presented with a superficial laceration on the belly, intestinal perforation, and extensive hand injuries.…”
Section: Discussionsupporting
confidence: 59%
“…One study on patients with traumatic brain injury showed that otolith organ specific hypofunction (pathological VEMPs, tilted subjective visual vertical) was diagnosed in 72% of patients suffering from dizziness, but only in 20% of those without dizziness 65 . Furthermore, reduced c- and oVEMP responses along with normal semicircular function are often found after blast trauma 66 .…”
Section: Acute Vestibular Syndromesmentioning
confidence: 99%
“…In einer Studie wurde bei Patienten mit Schwindel (« dizziness ») nach Schädel-Hirn-Trauma in 72% der Fälle ein einseitiges Otolithendefizit diagnostiziert (pathologische VEMPs, verkippte subjektive visuelle Vertikale), während die Patienten ohne Schwindel nach vergleichbarem Trauma nur in etwa 20% auffällige Befunde in der Funktionsprüfung der Otolithen-organe aufwiesen 65 . Auch nach Explosionstraumata finden sich gehäuft reduzierte c- und oVEMP-Antworten 66 .…”
Section: 12 Akute Einseitige Unterfunktion Der Otolithenorganeunclassified
“…Das heutige Feuerwerk hat seinen Ursprung in einer asiatischen Tradition, Bambus zu erhitzen, was zu typisch knallenden Geräuschen führt [ 8 ]. Das Feuerwerk soll zur Begrüßung des neuen Jahres allen Menschen Freude bringen und böse Geister vertreiben.…”
unclassified
“…Das Feuerwerk soll zur Begrüßung des neuen Jahres allen Menschen Freude bringen und böse Geister vertreiben. Beginnend mit dieser Tradition um 200 vor Christus [ 8 ] hat sich seither einiges geändert: Die Leuchteffekte wurden ausgefallener und farbenfroher, der gewünschte Klangeffekt blieb.…”
unclassified